Online Arbitration as a Form of Online Dispute Resolution on Foreign Investment Dispute in Indonesia - Angela Yohanna Hutagalung (International Journal Labs, 2023)
Online Arbitration is one the forms of Online Dispute Resolution (ODR), ODR itself is a form of Alternative Dispute Resolution (ADR) with the assistance of electronic media. This study provides a thorough analysis of the implementation of ODR in Foreign Investment Disputes in Indonesia. This research is also supported by a review of regulations and literature related to legal issues that the author studied. Related to the implementation and existence of Online Dispute Resolution, in Indonesia, there have been no specific regulations that regulate it. However, the existence of Law Number 30 of 1999 concerning Arbitration and alternative dispute resolution can be said to adequately support the validity of the online arbitration mechanism and verdict. Considering the digital advancement, the supply of ODR in an electronic or online-based transaction has become an urgent matter on this day. It is because of the potential dispute that may appear in the daily transactions.